2019
DOI: 10.1007/s00705-019-04194-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif

Abstract: Animal cells have multiple innate effector mechanisms that inhibit viral replication. For the pathogenic retrovirus human immunodeficiency virus 1 (HIV-1), there are widely expressed restriction factors, such as APOBEC3 proteins, tetherin/ BST2, SAMHD1 and MX2, as well as TRIM5α. We previously found that the TRIM5α gene clearly affects SIVmac or HIV-2 replication, but the major determinant of the combinatorial effect caused by multiple host restriction factors is still not fully clear. APOBEC3G (apolipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the case of A3H and Vif proteins, there is indeed a close coevolution [147]. A recent study investigated the presence of polymorphisms in A3G from Chinese rhesus macaques and their effect on infection by the virus HIV-2 [148]. The authors identified a variant of A3G, A3G L71R, which protects A3G from HIV-2 Vif-mediated degradation through a change of its conformation.…”
Section: Ubiquitination Of Apobec3 Is Useful For Virusesmentioning
confidence: 99%
“…In the case of A3H and Vif proteins, there is indeed a close coevolution [147]. A recent study investigated the presence of polymorphisms in A3G from Chinese rhesus macaques and their effect on infection by the virus HIV-2 [148]. The authors identified a variant of A3G, A3G L71R, which protects A3G from HIV-2 Vif-mediated degradation through a change of its conformation.…”
Section: Ubiquitination Of Apobec3 Is Useful For Virusesmentioning
confidence: 99%